Co-existence of Wuchereria bancrofti Microfilaraemia in a Case of Multiple Myeloma: An Incidental Finding or an Association? - Sonam Sharma; Rahul Mannan; Rachit Sharma; Sansar Chand Sharma (Journal of Clinical and Diagnostic Research, 2017)
Filariasis is a global health problem which is endemic in tropical and subtropical regions of Asia, Central and South America and Pacific Island nations. The most common parasite causing lymphatic filariasis in India is Wuchereria bancrofti, the microfilariae of which has been detected incidentally in fine needle aspirates and aspirated body fluids. However, its presence in the bone marrow aspirates is quite uncommon and that too in co-existence with a haematological malignancy. We report one such extremely rare case of Wuchereria bancrofti microfilaraemia in a multiple myeloma patient, which is the second case to be documented in the world literature to the best of our knowledge.